Do short sellers front-run insider sales? - KHAN, Mozaffar (Institutional Knowledge at Singapore Management University, 2013)
We study the behavior of short sellers as informed market participants and examine potential sources of their information. Using a newly available dataset with high-frequency short sales data, we find evidence of significant increases in short sales immediately prior to large insider sales, but not prior to small insider sales. We examine a number of explanations that the increase in short sales is driven by public information, either about the firm or about the impending insider sale. The evidence is inconsistent with these explanations, but is consistent with front-running facilitated by leaked information. The front-running appears to be concentrated in firms with poor accounting quality, suggesting that information about a large insider sale reinforces short sellers’ adverse opinion about firm value when accounting quality is poor.